2021
DOI: 10.2166/hydro.2021.166
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using smart meter water consumption data and in-sewer flow observations for sewer system analysis: a case study

Abstract: Globally, smart meters measuring the water consumption with a high temporal resolution at the consumers' households are deployed at an increasing rate. In addition to their use for billing or leak detection purposes, smart meters may provide a detailed knowledge of the wastewater inflow to the sewer systems in space and time and open up for new types of system analyses aimed at closing the urban water balance. In this study, we first validate the smart meter data against other, independent water distribution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…in different departmental systems) and by different external contractors, which makes integrated analysis tedious and resource demanding (e.g. Lund et al, 2021). We thus also encourage discussion on how the various information sources provided here may work together as required in future digital-twin environments (Pedersen et al, 2021b).…”
Section: Potential Use Of the Data Setmentioning
confidence: 94%
“…in different departmental systems) and by different external contractors, which makes integrated analysis tedious and resource demanding (e.g. Lund et al, 2021). We thus also encourage discussion on how the various information sources provided here may work together as required in future digital-twin environments (Pedersen et al, 2021b).…”
Section: Potential Use Of the Data Setmentioning
confidence: 94%
“…As the recovery of resources becomes a more important part of the WWTPs/WRRFs, this type of control is likely to become more prominently used in practice, providing the associated risks (see section 2.6) can be minimised. Using new data sources, like smart meters of water consumption, can generate more detailed picture of the DWF in a system (Lund et al 2021;Zhang et al 2021), opening new possibilities for DWF based RTC. Research in the potential of integrating this new data source has not been reported.…”
Section: Temporary Operational Changementioning
confidence: 99%
“…Within the concept of the nonstructural measures; MPC (Abou Rjeily et al, 2018; Zhao et al, 2019), RTC (Edmondson et al, 2018), and optimization techniques (Shishegar et al, 2018) have been widely used in combined sewer systems management. Smart storage tanks (Troutman et al, 2020), smart pipelines (Stoianov et al, 2007), wireless sensors (Montestruque, 2008), smart metering (Lund et al, 2021), smart sensors (Tatiparthi et al, 2021), cloud computing (Troutman et al, 2017), supervisory control, and data acquisition (SCADA; Larry, 2000) have also been used in data collection, control, and operation of sewer systems.…”
Section: Data‐driven Modeling and Operational Controlmentioning
confidence: 99%